Inhibitors of Clostridium histolyticum colagenase - Leite, Sérgio Roberto de Andrade (Eclética Química, 2018)
Different substances were tested as inhibitors of Clostridium histolyticum collagenase, both experimental and theoretically. The in vitro collagenase activity, alone and in the presence of inhibitors, was quantified by reaction with bovine collagen and dosage of the releasing amino acids. Collagenaseinhibitor interaction was studied theoretically by docking computational calculations. Only one among the tested substances showed inhibitor activity against the bacterial collagenase.